Room Temperature Light‐Mediated Long‐Range Coupling of Excitons in Perovskites. Issue 9 (1st March 2021) - Krisnanda, Tanjung; Zhang, Qiannan; Dini, Kevin; Giovanni, David; Liew, Timothy C. H.; Sum, Tze Chien
Abstract: Perovskites have been the focus of attention due to their multitude of outstanding optoelectronic properties and structural versatility. 2D halide perovskites such as (C6 H5 C2 H4 NH3 )2 PbI4, or simply PEPI, form natural multiple quantum wells with enhanced light–matter interactions, making them attractive systems for further investigation. This work reports tunable splitting of exciton modes in PEPI resulting from strong light–matter interactions, manifested as multiple dips (modes) in the reflection spectra. While the origin of the redder mode is well understood, that for the bluer dip at room temperature is still lacking. Here, it is revealed that the presence of the multiple modes originates from an indirect coupling between excitons in different quantum wells. The long‐range characteristic of the mediated coupling between excitons in distant quantum wells is also demonstrated in a structure design along with its tunability. Moreover, a device architecture involving an end silver layer enhances the two excitonic modes and provides further tunability. Importantly, this work will motivate the possibility of coupling of the excitonic modes with a confined light mode in a microcavity to produce multiple exciton‐polariton modes. Abstract : This work reports room temperature tunable excitonic mode splitting in 2D perovskite (C6 H5 C2 H4 NH3 )2 PbI4, possessing natural multiple quantum wells and exhibiting strong light–matter interactions. The origin of the mode splitting is revealed as a result of light‐mediated coupling of excitons in different quantum wells. The long‐range characteristic of the coupling and tunability of the resulting excitonic modes are demonstrated.